Role of Glial Cell-Derived Oxidative Stress in Blood-Brain Barrier Damage after Acute Ischemic Stroke. (2nd September 2022) - Hu, Xiaoyan; Wang, Yanping; Du, Weihong; Liang, Li-Jun; Wang, Wei; Jin, Xinchun
Abstract : The integrity of the blood-brain barrier (BBB) is mainly maintained by endothelial cells and basement membrane and could be regulated by pericytes, neurons, and glial cells including astrocytes, microglia, oligodendrocytes (OLs), and oligodendrocyte progenitor cells (OPCs). BBB damage is the main pathological basis of hemorrhage transformation (HT) and vasogenic edema after stroke. In addition, BBB damage-induced HT and vasogenic edema will aggravate the secondary brain tissue damage. Of note, after reperfusion, oxidative stress-initiated cascade plays a critical role in the BBB damage after acute ischemic stroke (AIS). Although endothelial cells are the target of oxidative stress, the role of glial cell-derived oxidative stress in BBB damage after AIS also should receive more attention. In the current review, we first introduce the physiology and pathophysiology of the BBB, then we summarize the possible mechanisms related to BBB damage after AIS. We aim to characterize the role of glial cell-derived oxidative stress in BBB damage after AIS and discuss the role of oxidative stress in astrocytes, microglia cells and oligodendrocytes in after AIS, respectively.